Consequences of divergence and introgression for speciation in Andean cloud forest birds. (1st July 2017) - Winger, Benjamin M.
Abstract: Divergence with gene flow is well documented and reveals the influence of ecological adaptation on speciation. Yet, it remains intuitive that gene exchange inhibits speciation in many scenarios, particularly among ecologically similar populations. The influence of gene flow on the divergence of populations facing similar selection pressures has received less empirical attention than scenarios where differentiation is coupled with local environmental adaptation. I used a paired study design to test the influence of genomic divergence and introgression on plumage differentiation between ecologically similar allopatric replacements of Andean cloud forest birds. Through analyses of short‐read genome‐wide sequences from over 160 individuals in 16 codistributed lineages, I found that plumage divergence is associated with deep genetic divergence, implicating a prominent role of geographic isolation in speciation. By contrast, lineages that lack plumage divergence across the same geographic barrier are more recently isolated or exhibit a signature of secondary genetic introgression, indicating a negative relationship between gene flow and divergence in phenotypic traits important to speciation. My results suggest that the evolutionary outcomes of cycles of isolation and divergence in this important theatre of biotic diversification are sensitive to time spent in the absence of gene flow.